Analisis Kepuasan Masyarakat Terhadap Penggunaan Instagram Menerapkan Metode Use Questionnaire - Befrizka Norzela; Joy Nashar Utama Jaya (Journal of Information System Research (JOSH), 2022)
Along with the times, the media for socializing is very diverse. The presence of social media at this time merges one's privacy space with the public. Today's community activities are also inseparable from social media. Online social media that is used as a means of social interaction online on the Internet. By using social media, its users can communicate with each other, interact, share, and various other activities. Of the many social media used today, one of the social media that is quite widely used is Instagram. Instagram itself is a social media platform that was founded on October 6, 2010. Instagram is a social media platform for applying digital filters and a place to upload and share photos with other users, but not infrequently Instagram is also one of the media to promote a product to the public. This is what makes the author want to examine the level of user satisfaction in North Penajam Paser Regency. raised a research entitled “Satisfaction Analysis of Social Media Use. The method in this study uses the Use Questionnaire method which has variables of Usefulness (usability), Ease of Use (ease of use), Ease of Learning (ease of learning), Satisfaction (satisfaction). This research uses quantitative descriptive research, which is based on the use of data in the form of numbers as an analysis tool and data acquisition through questionnaires in the field to 100 respondents. The results of this study note that the Usefulness Aspect scores 79.53%, the Ease of use aspect scores 82.42%, the Ease of learning aspect scores 83.70%, the Satisfaction Aspect scores 79.80%, and the final measurement results usability score percentage is 81.21%.